Associations between weight discrimination and metabolic health: A cross sectional analysis of middle aged adults. Issue 2 (March 2022) - Adil, Omar; Kuk, Jennifer L.; Ardern, Chris I.
Abstract: Background: Concurrent with the recent rise in overweight and obesity, concerns with weight discrimination have arisen. Individuals who have experienced weight discrimination report a host of deteriorations related to physical and psychological health, which may co-exist with behaviours such as increased food consumption and decreases in physical activity that make weight management difficult. What remains less clear, however, is the extent to which metabolic health may be specifically affected, and how this may vary by setting and perceived intensity of the lifetime history of weight discrimination. Method: To address this, a secondary data analysis was performed on 1365 participants from year 25 of the Coronary Artery Disease in Young Adults (CARDIA) study who were living with overweight and obesity. Descriptive statistics and logistic regression analyses were performed on the presence of metabolic syndrome, diabetes, and abdominal obesity, as well as their experience of the weight discrimination. Results: Prevalence of the metabolic syndrome, diabetes, and abdominal obesity was higher among those reporting low and high stress weight discrimination compared to those with no history of weight discrimination. In the adjusted analyses, weight discrimination was associated with a 65% greater likelihood for having metabolic syndrome, 85% greater likelihood of diabetes, and between a 2.5- and 3.9-times greater likelihood of abdominal obesity for low and high stress experiences, respectively. Conclusion: Exposure to weight discrimination may worsen metabolic health, as characterized by higher rates of metabolic syndrome and abdominal obesity. These associations may be greater with levels of stress experienced from weight discrimination. Further longitudinal work is necessary to understand the temporal sequence, time lag, and any possible critical periods for weight discrimination on metabolic health.